PROGNOSTIC SIGNIFICANCE OF THE EPITHELIAL-MESENCHYMAL TRANSITION MARKERS AND MORPHOLOGICAL CHARACTERISTICS OF HEAD AND NECK SQUAMOUS CELL CARCINOMAS IN THE DEVELOPMENT OF LYMPHOGENOUS METASTASES - V. A. Bychkov; L. N. Bondar; Ju. A. Nebova; I. V. Larionova; O. V. Cheremisina; V. M. Perelmuter (Сибирский онкологический журнал)
Previous studies of the morphological features of head and neck squamous cell carcinomas revealed a significant association of the presence of discrete tumor cells and a low level of inflammatory infiltrate with lymphogenous metastasis. The aim of the study was to evaluate the quantity of tumor cells undergoing epithelial-mesenchymal transition (EMt) in tumor cell structures of different degrees of differentiation and to assess the prognostic model of lymphogenous metastasis based on the studied parameters. Material and methods. the main clinical tumor characteristics and morphological patterns of the tumor were assessed in 92 patients. the expressions of snail and Vimentin proteins were studied in 16 patients using confocal microscopy. Results. the expression of the EMt marker in cell structures of different degrees of differentiation was evaluated; the maximum number of snail- and Vimentin-positive cells (20 % each) was observed in discrete tumor cells. No difference in the proportion of cells undergoing epithelial-mesenchymal transition between patients with and without lymphogenous metastasis was found. thus, the prognostic model of lymphogenous metastasis included: the presence of single tumor cells and low level of inflammation. the sensitivity of the model was 54.5 %, and specificity was 89 %.